Is Obesity a Modifiable Risk Factor for AF? - Hoyle, Brian (MD Conference Express, 2014)
Weight loss can reduce the effects of risk factors for atrial fibrillation (AF) and AF symptoms. Thus, weight reduction should be an important facet in the management of the obese patient with AF.